Managing cognitive resource expenditure and fostering creative thinking in biology teaching guided by instructional message design - Orbeta, Tristan C. (2022)
The mechanisms within the human cognitive architecture are an integral part of studies that involve knowledge acquisition, teaching approaches, and multimedia instructional design. However, there are limited investigations of these constructs in the context of learning biological concepts, particularly in actual classes. This study examined the effectiveness of a pedagogical intervention guided by instructional message design (IMD) principles in minimizing cognitive overloading while fostering creative thinking among high school biology students. It utilized a quasi-experimental approach and adopted the two-group repeated measures design. The study involved a total of 61 Grade 11 students from two comparable intact groups. The experimental group experienced IMD-guided biology teaching for a unit of instruction that lasted for 8 wk, totaling 10 class sessions. Data analysis through mixed ANOVA indicated that IMD-guided biology teaching was effective in lowering cognitive resource expenditure (CRE), whereas a one-way ANCOVA showed that the intervention was effective in enhancing student creative thinking. Also, analyses confirmed a negative relationship between CRE and creative thinking. The findings of this research have important implications for instructional design decisions and the development of biology instructional materials that are adapted across varied learning modalities. The use of IMD-guided biology teaching as a cognitive load-based intervention could facilitate the effective learning of complex biology topics by thoughtfully attending to the basic pedagogical components: content, teaching methodology, and instructional materials.
Keywords: Biology -- Study and teaching; Instructional design